Numerical simulation of ice-induced vibrations of steady-state type. Issue 12 (September 2019) - Qiu, Wenliang; Wu, Tianyu
Ice force is one kind of nonnegligible external loads that nature exerts on structures. The action of drifting ice floes may induce strong vibrations of offshore structures, and further reduce the structural safety and serviceability. The aim of this article is to develop a method to simulate the most dangerous situation during the interaction between ice and structure, that is, the ice-induced vibrations of steady-state type. A simulation methodology to realize structural steady-state vibration is proposed; it can simulate a special phenomenon of negative damping. The calculation of effective ice pressure is accomplished by an empirical formula which considers the dependence of the crushing strength on the ice velocity. The most important contribution of the simulation method is to capture the steady-state vibration phenomenon. The presented simulation methodology is conducted on the same model test introduced in a referenced study to verify the efficacy. Calculational examples show good agreements with the results of the model test, and the frequency contents of the generations coincide well with the targets. They directly prove the validity of the proposed simulation method. In addition, the numerical simulation method can be used in connection with finite element programs to perform a steady-state vibration analysis of offshore structures.